2016
DOI: 10.1108/jacpr-11-2015-0196
|View full text |Cite
|
Sign up to set email alerts
|

Frequent peer problems in Australian children and adolescents

Abstract: Purpose – Whilst overt bullying has received considerable attention for its negative impact on the emotional well-being of children and adolescents, peer problems such as excessive teasing and social exclusion have received less consideration. The purpose of this paper is to examine the prevalence, demographic, and clinical correlates of frequent peer problems in children and adolescents who participated in the Australian National Survey of Mental Health and Well-Being. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Further studies will be needed to focus on the association between teacher-student relationship and mental health problems among adolescents. This result is consistent with some previous studies, which indicated that peer problems can affect the emotional well-being of adolescents [55,56]. It has been shown that the psychological and behavioral characteristics of adolescents, such as externalizing and internalizing problems, were affected by their peers [57][58][59].…”
Section: Discussionsupporting
confidence: 92%
“…Further studies will be needed to focus on the association between teacher-student relationship and mental health problems among adolescents. This result is consistent with some previous studies, which indicated that peer problems can affect the emotional well-being of adolescents [55,56]. It has been shown that the psychological and behavioral characteristics of adolescents, such as externalizing and internalizing problems, were affected by their peers [57][58][59].…”
Section: Discussionsupporting
confidence: 92%
“…Girls also appeared to be more prone to internalizing problems compared with boys. These risk factors are likely to co-occur in many children (Denham et al, 2016; Gjerde et al, 2017) and also place children at risk of a number of other negative outcomes not confined to internalizing problems. As such, practitioners are encouraged to utilize the information holistically and consider the possibilities of co-occurrence of several risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Social Support and Family Functioning was assessed with the Multidimensional Scale of Perceived Social Support (MSPSS) 57 , which captures support from family, friends, and significant other 80 and two scales answered by the parent -the Alabama Parenting Questionnaire (APQ) 58 to capture parenting style and the McMaster Family Assessment Device (FAD) 59 , which provides both dimensional and overall measures of family functioning 81 . Peer influences and family factors are posited to influence adolescent brain development [82][83][84] and moderate adolescent risk of experiencing mental health problems [85][86][87][88] .…”
Section: Mental Healthmentioning
confidence: 99%
“…In addition, Social Support and Family Functioning was assessed with the Multidimensional Scale of Perceived Social Support (MSPSS) 60 , which captures support from family, friends, and significant other 83 and two scales answered by the parent -the Alabama Parenting Questionnaire (APQ) 61 to capture parenting style and the McMaster Family Assessment Device (FAD) 62 , which provides both dimensional and overall measures of family functioning 84 . Peer influences and family factors are posited to influence adolescent brain development [85][86][87] and moderate adolescent risk of experiencing mental health problems [88][89][90][91] . 54 × × Australian-adapted Hierarchical Personality Inventory for Children (HiPIC-A) 55 × Autism Spectrum Quotient -10 items (AQ-10) (Adolescent) 56 × Children's Response Styles Questionnaire -rumination subscale (CRSQ) 57 × × Children's Attributional Style Questionnaire -Revised (CASQ-R) 58 × × Early Adolescent Temperament Questionnaire -Revised (EATQ-R) 59 × × Social Support and Family Functioning Multidimensional Scale of Perceived Social Support (MSPSS) 60 × × Alabama Parenting Questionnaire (APQ; Parental Monitoring session 1 only) 61 × × McMaster Family Assessment Device (FAD) 62 × ×…”
Section: Mental Healthmentioning
confidence: 99%